Análisis de la evasión tributaria en los comerciantes del mercado central de Iquitos, periodo 2021 - Montes Chávez, Ambar Manuela (2021)
Tax evasion is a social phenomenon that is directly related to the evasive behavior exhibited by merchants in the face of voluntary compliance with their tax obligations regarding the commercial or economic activities they carry out, and that this phenomenon represents a voluntary action that contravenes the legal framework of our tax system and at the same time, it constitutes a crime against the public administration. The present investigation called "Analysis of tax evasion in the merchants of the Central Market of Iquitos, period 2021", had as a general objective to determine the level of tax evasion presented by merchants of the Central Market of Iquitos, period 2021. Likewise, the investigation It was of a quantitative type and of a descriptive, non-experimental - cross-sectional design. From the analysis and discussion of the results obtained, it was determined that the level of tax evasion presented by the merchants of the Central Market of Iquitos for the 2021 period was high.